115 Cardiovascular effects of living kidney donation: a five year longitudinal study. (17th July 2020) - Price, Anna; Moody, William; Stoll, Victoria; Vijapurapu, Ravi; Hayer, Manvir; Biasiolli, Luca; Weston, Chris; Webster, Rachel; Wesolowski, Roman; McGee, Kirsty; Edwards, Nicola; Liu, Boyang; et al.
Abstract : Background: The inverse association between estimated glomerular filtration rate (eGFR) and cardiovascular risk is well recognised but not fully explained. Kidney donation is known to reduce renal function by approximately 30% and allows the prospective study of the cardiovascular effects of a reduced eGFR in healthy subjects without confounding comorbidities. We report five year results in a group of kidney donors and healthy controls who underwent extensive cardiovascular assessment. Methods: A 5 year longitudinal, parallel group, blinded end-point study of living kidney donors (n=50) and healthy controls (n=45). Participants underwent office and 24-hr ambulatory blood pressure measures, multi-parametric cardiac magnetic resonance imaging (MRI) (3 Tesla), measurement of arterial stiffness (SphygmoCor), carotid intima-media thickness and blood and urine analysis at baseline, one year and 5 years from donation. Results: The eGFR in donors at baseline was 95 ± 15ml/min/1.73m2, 65 ± 13ml/min/1.73m2 at one year and 67 ± 14ml/min/1.73m2 at 5 years. Left ventricular (LV) mass was 112g at baseline in both groups and was not different at 5 years (113 ± 31 vs. 115 ± 30, p=0.707). There was also no difference in LV volumes, LV geometry, LV function, T1 times or extracellular volume (ECV) on MRI. Office and ambulatory blood pressures did not differ from controls at any time point. Pulse wave velocity was higher in donors at one year but not significantly different by 5 years. At 5 years, there was no significant differences in the prevalence of a detectable troponin or mean plasma NT pro-BNP. Conclusion: The stable reduction in eGFR to levels of 60-70 ml/min/1.73m2 after live kidney donation does not lead to deleterious changes in cardiovascular structure and function or biomarkers of cardiovascular disease at 5 years. Factors associated with kidney disease other than an isolated fall in eGFR are likely to explain the increased cardiovascular risk in patients with chronic kidney disease. Figure A and B : Longitudinal change in LV mass and PWV before and after donation in donors and controls. Black solid lines are means with confidence intervals for donors and dashed lines represent controls. Black squares indicate study visits. A; Left ventricular mass (g) and B; Adjusted pulse wave velocity (m/s) (adjusted for mean arterial pressure and heart rate). Conflict of Interest: None